2008
DOI: 10.1159/000178020
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Osteoblast Differentiation by Slit2 in Osteoblastic Cells

Abstract: Background/Aims: There is an urgent need to identify the molecular factors involved in osteoblast proliferation and differentiation in order to improve bone formation and treat bone disease. Recent studies demonstrate that many ‘axon guidance’ molecules play important roles in the development and remodeling of bone through their actions regulating osteoblast or osteoclast differentiation. The expressions and roles in bone tissue of the neuron guidance molecules slit and robo have not been reported previously. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 67 publications
1
35
1
Order By: Relevance
“…(39,40) Slit proteins, acting through their receptors Robo1/2, have been reported to inhibit osteoblast differentiation and function. (41) Finally, anti-NGF antibodies are undergoing testing in the clinic for the treatment of osteoarthritis and back pain, and one of the toxicities that has been well described is osteonecrosis of bone, although the mechanism for this toxicity has not been defined to date (42) and the effects of NGF (or NGF blockade) on bone metabolism have not been reported. Thus, although axonal guidance proteins and neurotrophins have been described to participate in bone remodeling, we hereby describe the unique role of Netrin-1 that acts both in an autocrine and a paracrine manner to synchronize osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…(39,40) Slit proteins, acting through their receptors Robo1/2, have been reported to inhibit osteoblast differentiation and function. (41) Finally, anti-NGF antibodies are undergoing testing in the clinic for the treatment of osteoarthritis and back pain, and one of the toxicities that has been well described is osteonecrosis of bone, although the mechanism for this toxicity has not been defined to date (42) and the effects of NGF (or NGF blockade) on bone metabolism have not been reported. Thus, although axonal guidance proteins and neurotrophins have been described to participate in bone remodeling, we hereby describe the unique role of Netrin-1 that acts both in an autocrine and a paracrine manner to synchronize osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…As the most commonly used oral antidiabetic drug, metformin was reported to be protective against bone loss [5]. As we know, osteoblast proliferation is the key element affecting bone health [12], so it is necessary to research on the influences from high glucose and metformin. In this study, CCK8 assay at day 3 and day 7 revealed that high glucose could suppress the proliferation of osteoblasts, while metformin could attenuate this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSCs) were harvested and cultured as described previously with modifications. Briefly, femora and tibiae were dissected free of surrounding soft tissues.…”
Section: Methodsmentioning
confidence: 99%